2008
DOI: 10.1086/526780
|View full text |Cite
|
Sign up to set email alerts
|

Maternal 12-Month Response to Antiretroviral Therapy following Prevention of Mother-to-Child Transmission of HIV Type 1, Ivory Coast, 2003- 2006

Abstract: Our study found that poor adherence and 3TC resistance acquired after the intervention to prevent mother-to-child transmission of HIV infection were associated with virologic failure in women who initiated antiretroviral treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
35
1
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 29 publications
3
35
1
2
Order By: Relevance
“…To prevent MTCT of HIV at about the time of delivery, a single dose of nevirapine (sdNVP) is administered at the start of labor and is the most common antiretroviral regimen used in resource-limited settings, as recommended by the World Health Organization (http://www.who.int/hiv/pub/mtct/en/arvdrugswomenguidelinesfinal .pdf). However, the use of sdNVP results in resistance mutations in 15 to 70% of women at 4 to 6 weeks postpartum (2,10,14), compromising the success of subsequent treatments with NVP in mother and child (7,19,15). The results of a recent clinical trial suggest that adding a single dose of tenofovir (TDF) and emtricitabine (FTC) at delivery may reduce those resistance rates by half (6).…”
mentioning
confidence: 99%
“…To prevent MTCT of HIV at about the time of delivery, a single dose of nevirapine (sdNVP) is administered at the start of labor and is the most common antiretroviral regimen used in resource-limited settings, as recommended by the World Health Organization (http://www.who.int/hiv/pub/mtct/en/arvdrugswomenguidelinesfinal .pdf). However, the use of sdNVP results in resistance mutations in 15 to 70% of women at 4 to 6 weeks postpartum (2,10,14), compromising the success of subsequent treatments with NVP in mother and child (7,19,15). The results of a recent clinical trial suggest that adding a single dose of tenofovir (TDF) and emtricitabine (FTC) at delivery may reduce those resistance rates by half (6).…”
mentioning
confidence: 99%
“…HIV-DNA level was also predictive of progression to immunodefi ciency when measured at the time of primary infection [ 8 ]. The high predictive value for disease progression results was also observed in a cohort of African patients [ 9 ]. In all studies, HIV-DNA levels were positively correlated to HIV-RNA and negatively to CD4 T cell count.…”
Section: Introductionmentioning
confidence: 58%
“…Previous studies reported that a single dose of NVP can already select drug-resistant viral strains in HIV-1-infected mothers (17,22), compromising subsequent maternal treatment success (8,25,29) and potentially promoting the transmission of NVP-resistant strains to the child during subsequent breastfeeding. We wanted to assess predictors for the selection of drug-resistant strains in HIV-1 infected mothers, which might subsequently lead to the transmission of resistant virus to the breastfed child.…”
Section: Resultsmentioning
confidence: 99%
“…However, the exact mechanism of HIV-1 prevention by NVP during intrapartum transmission remains unknown. Furthermore, owing to its long half-life, NVP frequently selects drug-resistant viral strains in HIVinfected mothers (17,22), which can compromise the efficacy of follow-up maternal and newborn antiretroviral treatment (ART) (8,25,29,39).…”
mentioning
confidence: 99%